LBA61A randomized phase II/III study to assess the efficacy of trametinib in patients with recurrent or progressive low-grade serous ovarian or peritoneal cancer. (1st October 2019) - Gershenson, D M; Miller, A; Brady, W; Paul, J; Carty, K; Rodgers, W; Millan, D; Coleman, R L; Moore, K N; Banerjee, S; Connolly, K; Secord, A A; et al.
Abstract: Background: Low-grade serous carcinoma of the ovary/peritoneum (LGSOC) is a rare subtype, accounting for 5-10% of all serous cancers, and is characterized by alterations in the MAPK pathway, relative chemoresistance, and prolonged overall survival (OS) compared to high-grade serous carcinoma. NRG Oncology in the US and the National Cancer Research Network (NCRN) in the UK collaborated on a phase II/III trial to assess the efficacy of a MEK inhibitor trametinib (TRAM) compared to physician's choice standard of care (SOC) in recurrent LGSOC. Methods: Patients (pts) were randomized 1:1 to receive either TRAM 2 mg daily or 1 of 5 SOC options (weekly paclitaxel, PLD, topotecan, letrozole, or tamoxifen) until disease progression. Pts who progressed on SOC were allowed to crossover to TRAM. The primary objective tested the progression-free survival (PFS) superiority of TRAM vs SOC. Secondary objectives included toxicity, QoL, and objective response rate (ORR) by RECIST 1.1. Exploratory objectives were OS and PFS and ORR after crossover. PFS and OS curves were estimated using the Kaplan-Meier method and compared by a 1-sided, α = 0.025 log-rank test. Results: 260 pts (48.1% had >3 prior lines of therapy) were enrolled between Feb 2014 and Apr 2018. Median follow-up was 31.4 months (mo). PFS was significantly improved for TRAM compared to SOC (median, 13.0 vs 7.2 mo; HR 0.48; 95% CI, 0.36-0.64; P < .0001). ORR was 26.2% for TRAM vs 6.2% for SOC (OR 5.4; 95% CI, 2.39-12.21; P< .0001). Response duration for TRAM was significantly better than for SOC (median, 13.63 mo; 95% CI, 8.08-18.76; vs 5.88 mo; 95% CI, 2.76-12.19). Preliminary analysis of QoL patient reported outcomes shows no significant therapy effects. Main Grade >3 AE in TRAM vs SOC were hematologic toxicity (13.4% vs 9.4%), GI toxicity (27.6% vs 29%), skin toxicity (15% vs 3.9%), and vascular toxicity (18.9% vs 8.6%). Median OS for TRAM vs SOC was 37.0 mo (95% CI, 30.3-NE) vs 29.2 mo (95% CI, 23.5-51.6) (HR 0.75; 95% CI, 0.51-1.11). For 88 pts who crossed over to TRAM, median PFS = 10.8 mo (95% CI, 7.3-12.0), and ORR = 15% (95% CI, 0.07-0.22). Conclusions: Compared to physician's choice SOC, TRAM was associated with significantly improved PFS and ORR in women with recurrent LGSOC. Clinical trial identification: NCT02101788. Legal entity responsible for the study: National Cancer Institute (NRG Oncology). Funding: National Cancer Institute (US) and Novartis. Disclosure: W. Brady: Full / Part-time employment: Sarah Cannon Development Innovations. R.L. Coleman: Advisory / Consultancy, Leadership role, Research grant / Funding (self), Non-remunerated activity/ies: AbbVie; Honoraria (self), Advisory / Consultancy: aravive; Honoraria (self), Honoraria (institution), Advisory / Consultancy, Research grant / Funding (self), Non-remunerated activity/ies: AstraZeneca; Honoraria (self), Honoraria (institution), Advisory / Consultancy, Research grant / Funding (institution), Travel / Accommodation / Expenses, Non-remunerated activity/ies: clovis; Honoraria (self), Advisory / Consultancy, Research grant / Funding (self), Research grant / Funding (institution), Travel / Accommodation / Expenses, Non-remunerated activity/ies: Roche Genentech; Honoraria (self), Research grant / Funding (self), Travel / Accommodation / Expenses, Non-remunerated activity/ies: Novartisjavascript:%20create_table_line('1', %20new%20Array('ent', %20'des', %20'tor'));; Honoraria (self), Research grant / Funding (institution), Travel / Accommodation / Expenses, Non-remunerated activity/ies: Janssen; Honoraria (self), Research grant / Funding (self), Research grant / Funding (institution), Travel / Accommodation / Expenses, Non-remunerated activity/ies: Merck; Honoraria (self), Advisory / Consultancy, Non-remunerated activity/ies: Immunogen; Honoraria (self), Advisory / Consultancy, Travel / Accommodation / Expenses: Tesaro/GSK; Honoraria (self), Research grant / Funding (institution), Travel / Accommodation / Expenses, Non-remunerated activity/ies: Genmab; Honoraria (self), Advisory / Consultancy, Travel / Accommodation / Expenses: Gamamab; Honoraria (self), Advisory / Consultancy, Research grant / Funding (self), Research grant / Funding (institution), Travel / Accommodation / Expenses, Non-remunerated activity/ies: Oncomed; Honoraria (self), Advisory / Consultancy: Agenus; Research grant / Funding (self), Research grant / Funding (institution): NCI-SPORE. K.N. Moore: Honoraria (institution), Advisory / Consultancy: Clovis. S. Banerjee: Honoraria (self), Research grant / Funding (institution), Travel / Accommodation / Expenses: AstraZeneca; Honoraria (self), Research grant / Funding (institution), Travel / Accommodation / Expenses: Tesaro; Honoraria (self): Clovis; Honoraria (self): Merck Sereno; Honoraria (self): Seattle Genetics; Honoraria (self), Travel / Accommodation / Expenses: Roche; Honoraria (self): PharmaMar; Research grant / Funding (institution): Janssen Cilag; Honoraria (self), Travel / Accommodation / Expenses: Gamamabs. A.A. Secord: Research grant / Funding (institution): AbbVie, Amgen, Astellas Pharma Inc., AstraZeneca, Boehringer Ingelheim, Bristol-Myers Squibb, Clovis, Eisai, Endocyte, Exelixis, Incyte, Merck, PharmaMar, Immutep Ltd, Roche/Genentech, Seattle Genetics, Inc, TapImmune and Tesaro; Honoraria (self): Aravive, AstraZeneca, Clovis, Janssen/Johnson & Johnson, Merck, Mersana, Oncoquest, Roche/Genentech, and Tesaro . D.M. O'Malley: Honoraria (self), Advisory Board: Genelux; Honoraria (self), Research grant / Funding (institution), Advisory Board: Eisai; Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution): GOG Foundation; Honoraria (self): NCCN; Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution): Immunogen; Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution), Advisory board, Steering Committee: Clovis; Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution), Advisory board: Abbie, Iovance ; Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution), US PI/Steering Committee: Novocure; Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution), Advisory board, Steering Committee: Tesaro; Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution), Advisory board, steering Committee: AstraZeneca; Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution), Advisory board, PI, Steering Committee: Agenus; Honoraria (self), Advisory / Consultancy, Advisory board: OncoQuest; Honoraria (self), Advisory / Consultancy, Advisory board: Ambry; Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution): Genentech; Research grant / Funding (institution): Regeneron; Research grant / Funding (institution): AMGEN, BMS; Research grant / Funding (institution): Array Biopharma, inVentiv ; Research grant / Funding (institution): Janssen, Tracon; Research grant / Funding (institution): EMD Serono; Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution), Advisory board: Leap Therapeutics. O. Dorigo: Advisory / Consultancy, Speaker Bureau / Expert testimony: Tesaro; Speaker Bureau / Expert testimony: AstraZeneca; Advisory / Consultancy: Clovis; Advisory / Consultancy: Merck. S. Gaillard: Research grant / Funding (institution): Pfizer, Bristol-Myers Squibb, Genentech/Roche, Gradalis, Iovance Biotherapeutics, Merck, PharmaMar, TetraLogic Pharmaceuticals, AbbVie; Advisory / Consultancy: AstraZeneca, Immunogen. C. Gourley: Honoraria (self), Honoraria (institution), Advisory / Consultancy, Research grant / Funding (institution), Travel / Accommodation / Expenses: AstraZeneca; Honoraria (self), Honoraria (institution), Advisory / Consultancy: Roche; Honoraria (self), Honoraria (institution), Advisory / Consultancy, Research grant / Funding (institution), Travel / Accommodation / Expenses: MSD; Honoraria (self), Honoraria (institution), Advisory / Consultancy, Research grant / Funding (institution), Travel / Accommodation / Expenses: Tesaro; Honoraria (self), Honoraria (institution), Advisory / Consultancy, Research grant / Funding (institution): Nucana; Honoraria (self), Honoraria (institution), Advisory / Consultancy, Travel / Accommodation / Expenses: Clovis; Honoraria (self), Honoraria (institution), Advisory / Consultancy, Travel / Accommodation / Expenses: Foundation One; Honoraria (self), Honoraria (institution), Advisory / Consultancy: Sierra Oncology; Honoraria (self), Honoraria (institution), Advisory / Consultancy, Travel / Accommodation / Expenses: Cor2ED; Research grant / Funding (institution): Novartis; Research grant / Funding (institution): Aprea. All other authors have declared no conflicts of interest.